The Effectiveness of Providing Educational Videos on the Management of Lethal Arrhythmias on Nurses’ Knowledge and Skills in the Inpatient Unit - Adnyani, Putu Desi; Agustini, Ni Luh Putu Inca Buntari; Wahyunadi, Ni Made Dewi; Sanjana, I Wayan Edi (Babali Nursing Research, 2025)
Introduction: Patients undergoing hospitalization are at risk of sudden cardiac arrest, necessitating swift and accurate intervention from nurses. The preparedness and confidence of nurses in such situations significantly impact the desired outcomes. Basic and advanced life support training is crucial and can be delivered through various media, including instructional videos. This study aims to evaluate the effectiveness of learning videos on the management of lethal arrhythmias in improving the knowledge and skills of nurses at the inpatient unit of Mangusada Hospital. Methods: This study utilized a quasi-experimental design with a Non-Equivalent Control Group Design. The sample comprised 60 inpatient nurses, 30 in the control and 30 in the treatment group. Data was collected using questionnaires, checklists, and instructional videos. Data analysis was conducted using univariate and bivariate analyses with the Wilcoxon Signed Rank Test and Mann-Whitney Test. Results: There were significant differences in nurses' knowledge (p-value = 0.003) and skills (p-value = 0.040) between the control and treatment groups, with learning videos being more effective in enhancing nurses' knowledge and skills in managing lethal arrhythmias at the inpatient unit of Mangusada Hospital. Conclusion: Learning videos effectively improve nurses' knowledge and skills, though they have limitations, particularly regarding skills. Continuous direct action or simulation training, combined with learning videos, is essential. It is recommended that such training be conducted twice a year.